A review of the role of the Cucurbitaceae family in food security in West Africa - Olufunke O. Fajinmi; Olaoluwa O. Olarewaju; Georgina D. Arthur; Kuben Naidoo; Roger M. Coopoosamy (AOSIS, 2022)
Background: Food and nutritional security are main development goals in several countries of Africa. In West Africa, the use of African indigenous vegetables caters for the food and nutritional needs of a high proportion of the people, most particularly amongst the poor and rural dwellers. The family Cucurbitaceae is one of the most important and widely grown vegetables in the tropical and subtropical climates. Aim and objective: This review discusses the culinary relevance of several species of Cucurbitaceae and their roles in food security in West Africa. Methods: A literature search was conducted on electronic databases such as Google Books, Google Scholar, Scopus and Web of Science. Discussions: Certain genera such as Telfairia, Cucurbita and Citrullus and other Egusi species are commonly cultivated in different parts of West Africa including Nigeria for their fruits, seeds and leaves because of their crucial nutrient compositions and palatability in local diets. These species and other species of Cucurbitaceae are used as traditional vegetables or African indigenous vegetables and are either sourced from the wild or cultivated in several African countries. Some of these species have played roles beyond food security but have also been crucial tools for nutritional security, especially within the low-income group and rural communities. Conclusions: Several communities in West Africa use almost all parts of the plant (leaves, fruit, seed, flowers) of some species of this family as food or in food preparations. Their use could also lead to innovative pathways towards reducing diseases associated with malnutrition especially those related to protein deficiency.